Control of low-temperature polyoxymethylene dimethyl ethers (PODEn)/gasoline combustion considering fuel concentration, fuel reactivity, and intake temperature at low loads. (15th February 2023) - Duan, Huiquan; Jia, Ming; Wang, Hui; Li, Yaopeng; Xia, Guangqing
Highlights: The control mechanism of low-temperature PODEn /gasoline combustion was revealed. The collaborative organization of fuel reactivity and concentration dominates PPC. Reliable control can effectively be achieved at the PR of 14.9% for R-RCCI. R-RCCI can achieve 26% reduction in NOx emissions compared with PPC. Lower T in is required for R-RCCI to achieve stable combustion than PPC. Abstract: This study aims to investigate the control mechanism of fuel properties and intake temperature ( T in ) on the low-temperature polyoxymethylene dimethyl ethers (PODEn )/gasoline combustion to maximize the advantages of PODEn in enhancing engine performance. To achieve this goal, two representative combustion modes of partially premixed combustion (PPC) and reactivity-controlled compression ignition with reverse reactivity stratification (R-RCCI) with different fuel regulating methods were investigated. In PPC, the fuel was regulated by blending PODEn and gasoline outside the cylinder, while for R-RCCI, the in-cylinder fuel was tuned by delivering the two fuels into the cylinder with two different fuel supply systems. The main factors dominating the combustion process and pollutant emissions were identified for these two combustion modes. The results show that the combustion process of PPC is dominated by the collaborative organization of fuel reactivity and concentration in the cylinder, and 50% burn point (CA50) plays only a secondary role, but CA50 determines the nitrogen oxides (NOx ) emission level. For PPC operated with the start of injection later than −40 °CA ATDC, increasing local fuel concentration is more effective in improving the combustion efficiency and indicated thermal efficiency than increasing T in . For R-RCCI, the lower local temperature caused by the heat of vaporization of the directly injected gasoline remarkably influences the combustion process, but this cooling effect is not significant in PPC. The comparison of PPC and R-RCCI shows that the in-cylinder local fuel reactivity impacts the ignition more significantly than the overall fuel reactivity. Compared with PPC, R-RCCI can effectively reduce combustion instability and combustion rate, and simultaneously 26% reduction in NOx emissions was accomplished.